Differences in horizontal and vertical mismatches across countries and fields of study. (March 2017) - VERHAEST, Dieter; SELLAMI, Sana; van der VELDEN, Rolf
Abstract: Based on early career data on graduates in Europe and Japan, the authors investigate whether full job mismatch (i.e. field‐of‐study mismatch and over‐education), mere horizontal mismatch and mere vertical mismatch can be explained by differences in institutions and labour market imbalances. Mere horizontal mismatch is lower in countries with stronger employment protection, higher unemployment benefits and selective educational programmes. Cross‐country differences in mere vertical mismatch are largely explained by labour market imbalances. These variables also affect full mismatch, which is positively related to collective bargaining coverage as well. Field‐of‐study differences in mismatches are similarly determined by educational programme characteristics and labour market imbalances.